Investigating the role of social media in tourism promotion: a case study from Egypt (2019-2021) - Eman El Shamy; Samy Tayie; Maria José Recoder (Insights into Language, Culture and Communication)
The aim of this study is to investigate about the role of social media in promoting tourism using Egypt as a case study. By examining the topic from the perspective of international and domestic tourists (the demand side) and from the perspective of Egyptian tourism providers (the supply side). This study applied a mixed methods approach i.e., quantitative, and qualitative methods. The findings show that travel companies in Egypt did not exploit the benefits of social media and the main obstacle facing them was the existence of fake companies that take from their market share and ruin the reputation of Egypt, in consequences they want the government to have a supervisory role over them. Concerning Egyptian Tourism Authority, they didn’t seem to have an online strategy in 2019, the situation improved in 2020 and in 2021 their online branding strategy was obvious. From the perspective of tourists (domestic and international), an open-ended question in the questionnaire sent to them allow to know about their recommendations for an effective tourism promotion through social media. Both domestic and international tourists recommend stopping fake products, to have transparency and to make price lists of services and attractions. To promote Egypt in more innovative ways such as promoting culture and local food and sharing real people experiences.   Received: 08 March 2023 Accepted: 29 March 2023 Published: 20 April 2023